Case report: Short-long-short mechanism triggering sustained ventricular tachycardia in a patient with a single-chamber ICD but inhibiting antitachycardia therapy - Schernthaner, Christiana; Topf, Albert; Motloch, Lukas J.; Kraus, Johannes; Hauptmann, Laurenz; Hoppe, Uta C.; Strohmer, Bernhard (Frontiers in Cardiovascular Medicine, 2022)
Introduction Short-Long-Short (S-L-S) sequences are an important cause of ICD pro-arrhythmia and can initiate both polymorphic and monomorphic ventricular tachycardias (VT). Depending on the programming of some devices, the S-L-S sequence can be responsible for critical limitations of the detection criteria for sustained VT finally withholding adequate anti-tachycardia pacing or shock therapy. Methods A 78-year-old ICD patient was admitted after external cardioversion of a long-lasting VT with hemodynamic compromise. The interrogation of the ICD revealed a S-L-S sequence initiating a monomorphic VT at a rate of 171 bpm (350 ms). VT discrimination of the implanted single-chamber ICD was based on Onset and Stability criteria as the patient had a history of paroxysmal atrial fibrillation. The ICD was programmed that both criteria had to be met for VT detection and initiation of antitachycardia therapy. Results Due to the S-L-S sequence in combination with the programmed VT detection interval the Onset threshold was not fulfilled and inhibited adequate therapy. Some relatively slow VT beats following the S-L-S sequence resulted finally in a considerable delay for the declaration of the episode onset. As a first step, the threshold for VT detection was programmed to 150 bpm instead of 160 bpm. To avoid S-L-S sequences and pause dependent ventricular tachyarrhythmias, VVI backup stimulation was increased from 35 ppm to 55 ppm. Besides, a device-specific algorithm, called rate smoothing, was activated as a potential preventive feature. At a three-month follow-up, all sustained VT episodes were detected adequately by the reprogrammed device, resulting in appropriate antitachycardia pacing. The patient remained free of symptoms and arrhythmias over a follow-up of more than 2.5 years. Conclusions S-L-S sequences may initiate or trigger VT episodes. Misclassification of the true onset may occur related to specific programming of VT detection criteria in some ICD devices finally inhibiting therapy. Antibradycardia backup pacing at a very low stimulation rate may facilitate S-L-S sequences in ICD patients resembling a potential proarrhythmic mechanism. In case of a gradual VT onset with some intervals slower than the programmed VT threshold, the detection rate has to be adjusted down to guarantee appropriate identification of the onset.